Enhancing Added Value of Village Agriculture Sector through Strengthening the Capacity of BUMDes Based on Digital Economy - Hajar Dewantara; Basri Bado; Sitti Hasbiah; Ilma Wulansari Hasdiansa; Andi Anggi Kemalasari (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
Village-owned enterprises (BUMDes) are institutions established to manage economic potential and resources in the village to improve community welfare. In Kassi Village, Jeneponto Regency, BUMDes has significant potential in developing the agricultural sector, but this potential has not been fully utilized. This research aims to increase the added value of the agricultural sector through strengthening the capacity of BUMDes by utilizing digital technology. The application of e-commerce, digital marketing, and data management is expected to expand market access for local products and improve their competitiveness. The methods used include identification of training needs, ongoing mentoring, and monitoring and evaluation of the BUMDes digitalization process. The program results show an increase in operational efficiency and expansion of marketing networks, as well as an increase in the added value of agricultural and tourism products. Analysis shows that the training on sustainable agriculture and basic technology has had a significant impact on improving participants' knowledge and skills, as evidenced by the increase in average pretest to posttest scores. The high correlation between the initial and final scores indicates that the training was effective for all participants. This digital transformation through BUMDes has the potential to become a model for other villages in Indonesia, making digital economic empowerment a strategic solution to improve the welfare of rural communities in an inclusive and sustainable manner.